Real-Time Macro Monitoring and Fiscal Policy - Ley, Eduardo (World Bank, Washington, DC, 2013)
This paper considers the effects of inaccurate real-time output data on fiscal management, both with respect to budgetary planning and fiscal surveillance. As newer and better information becomes available, output data available in real time get revised and are likely to conflict with final figures that are only released some years later. Nevertheless, fiscal policy needs to be inevitably based on real-time figures. The paper develops a simple modeling framework to formalize these linkages and combines it with a newly compiled dataset from the International Monetary Fund's World Economic Outlook, comprising final and real-time output data for 175 countries, over a period of 17 years. We simulate the effects of output revisions on revisions of the overall balance, the structural balance and debt accumulation. It finds that output revisions may have substantial effects on the ability of governments to correctly estimate the overall balance and the structural fiscal balance in real time, and that the effects may imply substantial debt accumulation.